2016
DOI: 10.1590/1678-98652016000100004
|View full text |Cite
|
Sign up to set email alerts
|

Stages of change and factors associated with misperceived eating behavior in obese individuals

Abstract: Objective: To evaluate the stages of behavior change related to fat and fruit/vegetable intakes and the factors associated with misperceived eating behavior (pseudo-maintenance). Methods: This cross-sectional study collected sociodemographic, socioeconomic, health, and food intake data from obese individuals (n=103) aged ≥20 years. Stages of behavior change according to the Transtheoretical Model were measured for fat and fruit/vegetable intakes. The pseudo-maintenance stage was reclassified in subjects in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
5
1
1
Order By: Relevance
“…As for national investigations, only two studies that assessed the reclassification in PM and/or NRA for FV intake were found [11,16]. However, the comparison of the results with the present study proved to be inadequate due to the different groups studied and methodologies used to classify and reclassify the stages of change, which reveals the lack of reproducibility of current national studies in this field.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…As for national investigations, only two studies that assessed the reclassification in PM and/or NRA for FV intake were found [11,16]. However, the comparison of the results with the present study proved to be inadequate due to the different groups studied and methodologies used to classify and reclassify the stages of change, which reveals the lack of reproducibility of current national studies in this field.…”
Section: Discussioncontrasting
confidence: 68%
“…The PAS was chosen for this study because of its unique characteristics concerning health promotion, which are intrinsically related to the intake of FV, its focus on empowerment and autonomy of the participants, and its recent implementation in the SUS. A study conducted on the perception of food intake in this healthcare service found 19.4% of pseudo-maintenance for FV intake (assessed as a single group) among obese individuals [11].…”
Section: E T H O D Smentioning
confidence: 98%
See 3 more Smart Citations